2021
DOI: 10.1002/brb3.2230
|View full text |Cite
|
Sign up to set email alerts
|

Test‐retest and time dependent variation and diagnostic values of vibratory sensation determined by biothesiometer and the Rydel‐Seiffer tuning fork

Abstract: Background and aims: Polyneuropathy is a common neurological disorder with many potential causes. An essential part in screening, diagnosis, and follow-up evaluation of polyneuropathy is testing of the sensory function including vibratory sensation. The graduated Rydel-Seiffer tuning fork and the biothesiometer have been developed to quantify vibratory sensation through detection thresholds. The aim of this study is to compare the vibration detection thresholds determined by the two instruments regarding intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In our case, the differences were found in results between neurothesiometer and diapason measures: we observed a closer relationship between altered gait parameters and sensory vibration loss measured by the neurothesiometer in bivariate analysis. A recent study 68 concluded that there was no difference between the Rydel‐Seiffer diapason and the neurothesiometer in the polyneuropathy diagnosis for both clinical and research purposes, although diabetic patients were not included in this research. Of all the sensory variables considered in our study, ‘the presence of sensory neuropathy,’ established by the combination of monofilament and VPT by neurothesiometer, was the variable that was related to the most gait abnormalities, which reinforces the importance of both deep sensory modalities during walking.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the differences were found in results between neurothesiometer and diapason measures: we observed a closer relationship between altered gait parameters and sensory vibration loss measured by the neurothesiometer in bivariate analysis. A recent study 68 concluded that there was no difference between the Rydel‐Seiffer diapason and the neurothesiometer in the polyneuropathy diagnosis for both clinical and research purposes, although diabetic patients were not included in this research. Of all the sensory variables considered in our study, ‘the presence of sensory neuropathy,’ established by the combination of monofilament and VPT by neurothesiometer, was the variable that was related to the most gait abnormalities, which reinforces the importance of both deep sensory modalities during walking.…”
Section: Discussionmentioning
confidence: 99%
“…The weakest vibration intensity the patient was able to perceive was recorded. Vibratory sensation was considered deficient when the participant was unable to perceive the stimulus at 25 volts or more on the dorsal area of the big toe [ 67 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Voltage is subsequently increased or decreased according to a protocol, and the subject reports their perceptions [31]. Vibrational QST has been shown to perform comparably but not better than the Rydel-Seiffer tuning fork (used in neurologic physical examination) in predicting the detection of neuropathy [32]. Therefore, the tuning fork, the simpler method, may be preferred [16].…”
Section: What Qst Testsmentioning
confidence: 99%